2021
DOI: 10.3390/foods10071581
|View full text |Cite
|
Sign up to set email alerts
|

Fruit Quality Characteristics and Biochemical Composition of Fully Ripe Blackberries Harvested at Different Times

Abstract: We investigated how the quality of blackberry fruit changes during the ripening period. Since it is difficult to predict picking dates for blackberries, we were interested in how the quality of fully ripe fruit changed depending on the sampling date (from 28 July to 1 September). Blackberries (at full ripeness) were sampled at six weekly intervals and the contents of sugars, vitamin C, organic acids and phenolic components were analysed by high performance liquid chromatography combined with mass spectrometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Therefore, the TSS and soluble sugar content of most samples decreased during postharvest storage. In this study, the value of TSS and soluble sugar content were approximate to that in the research of Mikulic‐Petkovsek et al (2021). However, the ripening in postharvest stage may also elevate the TSS and soluble sugar content, explaining the increase of TSS in “Arapaho” and soluble sugar content in some cultivars at the beginning of the storage (Huang et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Therefore, the TSS and soluble sugar content of most samples decreased during postharvest storage. In this study, the value of TSS and soluble sugar content were approximate to that in the research of Mikulic‐Petkovsek et al (2021). However, the ripening in postharvest stage may also elevate the TSS and soluble sugar content, explaining the increase of TSS in “Arapaho” and soluble sugar content in some cultivars at the beginning of the storage (Huang et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, the TSS and soluble sugar content of most samples decreased during postharvest storage. In this study, the value of TSS and soluble sugar content were approximate to that in the research ofMikulic-Petkovsek et al (2021). However, the ripening in postharvest stage may also elevate the TSS and solubleF I G U R E 6 Antioxidant activity in fruit of six blackberry cultivars stored at 25°C, 55% RH for 4 days (RT) or 4°C, 90% RH for 10 days (LT).…”
supporting
confidence: 50%
“…There were high contents of cyanidin-3- O -glucoside and cyanidin-3- O -rutinoside on either side (fractions 13–15 and 18–21) of flash fractions 16 and 17, and these two anthocyanins could be responsible for high antioxidant indices. Reyes-Carmona et al [ 35 ] have also shown that there is a significant correlation among antioxidant activities, namely FRAP and oxygen radical absorbance capacity (ORAC), and the concentration of cyanidin-3-O-glucoside and cyanidin-3- O -rutinoside in blackberries. Similarly, Gong et al [ 4 ], through boosted regression tree analysis, also showed that cyanidin-3- O -glucoside and chlorogenic acid were the main contributors in the antioxidant activity of free phenolics from different blackberry varieties.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that both sugars and organic acids are the main water-soluble substances in berries and play a crucial role in developing the taste and in the process of ripening of blackberries, as well as being a qualitative index of how they will be appreciated by consumers. Thus, organic acids together with sugars and their properties, along with various secondary and aromatic metabolites determine the taste and organoleptic properties of fruits [MIKULIC-PETKOVSEK & al. 2021].…”
Section: Resultsmentioning
confidence: 99%